2017
DOI: 10.1093/hmg/ddx282
|View full text |Cite
|
Sign up to set email alerts
|

Metalloprotease-mediated cleavage of PlexinD1 and its sequestration to actin rods in the motoneuron disease spinal muscular atrophy (SMA)

Abstract: Cytoskeletal rearrangement during axon growth is mediated by guidance receptors and their ligands which act either as repellent, attractant or both. Regulation of the actin cytoskeleton is disturbed in Spinal Muscular Atrophy (SMA), a devastating neurodegenerative disease affecting mainly motoneurons, but receptor-ligand interactions leading to the dysregulation causing SMA are poorly understood. In this study, we analysed the role of the guidance receptor PlexinD1 in SMA pathogenesis. We showed that PlexinD1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 71 publications
1
10
0
Order By: Relevance
“…The rod response is mimicked by a specific agonist to the subclass of glutamate receptors responsive to AMPA (α-amino-3-hydroxy-5methyl-4-isoxazolepropionic acid) [285]. More mature neurons, 10-14 DIV, utilized both AMPAR and the calcium-permissive NMDA (N-methyl-D-aspartate) receptors for rod induction, which also occurs during a similar time course [286]. SSH1 dephosphorylation by calcineurin may be the mechanism activating cofilin [96].…”
Section: Rods Induced By Excitotoxicitymentioning
confidence: 99%
“…The rod response is mimicked by a specific agonist to the subclass of glutamate receptors responsive to AMPA (α-amino-3-hydroxy-5methyl-4-isoxazolepropionic acid) [285]. More mature neurons, 10-14 DIV, utilized both AMPAR and the calcium-permissive NMDA (N-methyl-D-aspartate) receptors for rod induction, which also occurs during a similar time course [286]. SSH1 dephosphorylation by calcineurin may be the mechanism activating cofilin [96].…”
Section: Rods Induced By Excitotoxicitymentioning
confidence: 99%
“…PlexinD1 is a receptor for class 3 semaphorins and acts as a signalling factor to guide axonal growth. In the Taiwanese mouse model and in iPSC-derived motor neurons from SMA patients, PlexinD1 was shown to be cleaved by metalloproteases, resulting in its functional change from being an attractant to a repellent signalling factor, thereby contributing to growth cone collapse [ 145 ]. In the same study, cleaved PlexinD1 was found to be enriched in actin rods, a pathological structure of elongated actin aggregates also found in some age-related neurodegenerative diseases but not in control cells.…”
Section: Smn and The Cytoskeletonmentioning
confidence: 99%
“…Labelling of cofilin-actin rods was performed as described in ref. 22 . Briefly, neurons were rinsed once with KRH-EGTA, fixed 10 min with 4% paraformaldehyde, 4% sucrose in 120 mM sodium phosphate buffer, pH 7.4, supplemented with 2 mM EGTA, and permeabilized with methanol at −20°C for 10 min followed by 20 min in 1% Triton X-100, 4% horse serum (HS) in PBS.…”
Section: Cell Labelling Protocols and Image Acquisitionmentioning
confidence: 99%